3 Archeologicke Pamiatky a sucasnost : Bratislava jul 1984. (Bratislava : The Bratislava City Board, 1984)
Adamciak, Milan ; Bahna, Jan ; Simkovic, Vladimir ; Bartusz, Juraj ; Bauer, Pavol ; Beran, Anton ; Borecka, Eva ; Botek, Andrej ; Polomova, Beata ; etc.
Archaeological monuments and present : The Relict of the Middle Age town gate with regard to the present town, The Bratislava City Board of the Care of Historical Monuments and Preservation of Nature, Bratislava, july 1984
boek